Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/eji.200838904
|View full text |Cite
|
Sign up to set email alerts
|

Loss of FOXP3 expression in natural human CD4+CD25+ regulatory T cells upon repetitive in vitro stimulation

Abstract: The adoptive transfer of CD4 1 CD25 1 natural regulatory T cells (Treg) is a promising strategy for the treatment of autoimmune diseases and the prevention of alloresponses after transplantation. Clinical trials exploring this strategy require efficient in vitro expansion of this rare cell population. Protocols developed thus far rely on high-grade purification of Treg prior to culture initiation, a process still hampered by the lack of Treg cell-specific surface markers. Depletion of CD127 1 cells was shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
273
3
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 312 publications
(302 citation statements)
references
References 35 publications
20
273
3
1
Order By: Relevance
“…However, this might not intrinsically be limited to iTreg since it has recently been shown that nTreg can also turn into Th17 effector cells after transfer into lymphopenic hosts [24]. Along the same lines, human nTreg have been reported to lose Foxp3 expression after repetitive TCR stimulation [25]. Intriguingly, we find that approximately $80% of the transferred nTreg stably remain Foxp3 1 even in the lymphopenic and inflammatory environment of acute GVHD.…”
Section: Resultssupporting
confidence: 57%
“…However, this might not intrinsically be limited to iTreg since it has recently been shown that nTreg can also turn into Th17 effector cells after transfer into lymphopenic hosts [24]. Along the same lines, human nTreg have been reported to lose Foxp3 expression after repetitive TCR stimulation [25]. Intriguingly, we find that approximately $80% of the transferred nTreg stably remain Foxp3 1 even in the lymphopenic and inflammatory environment of acute GVHD.…”
Section: Resultssupporting
confidence: 57%
“…Mature moDC-expanded nTregs express high levels of FOXP3 and maintain the TSDR-demethylation status within the FOXP3 gene Long-term cultures of nTregs may result in loss of the nTregphenotype identified by diminished FOXP3 expression, which is associated with loss of suppressive capacity (47)(48)(49). In accordance with a previous publication (11), .90% of the freshly isolate nTregs expressed FOXP3, in contrast with a very low expression in T cells depleted for nTregs (effector T cells) (11).…”
Section: Allogeneic Mature Modcs Are Superior In Expanding Ntregssupporting
confidence: 85%
“…First, adaptive Foxp3 + Tregs in vitro appear to lose Foxp3 expression on restimulation without TGF-b and their TSDR demethylation levels, although higher than those of Th cells, were much lower than those of CD4 + CD25 high Tregs (26). Second, progressive loss of Foxp3 expression on repetitive in vitro stimulation has been reported in sorted CD4 + CD25 high CD127 2 Tregs as well as in CD4 + CD25 high CD45RA + Treg clones (40). In this study, the loss of Foxp3 expression was associated with the very heterogeneous profiles of Foxp3 expression between Treg clones as is the case for the TA-specific clones in our study.…”
Section: Discussionmentioning
confidence: 99%